KORELASI GENETIKA SIFAT PRODUKSI SEBAGAI DASAR PEMILIHAN DOMBA LOKAL GENETIC CORRELATION OF PRODUCTION CHARACTERISTICS AS BASES FOR SELECTION OF INDIGENOUS SHEEP - Santosa, Setya Agus; Sudewo, A.T Ari; Purwantini, Dattadewi (Pembangunan Pedesaan, 2006)
Aims of this research were to know genetic correlation of birth and weaning weight of indigenous sheep. Materials used were 240 birth and weaning weight recorded from 100 days of the indigenous lambs age that were born from 40 dams mated by 8 rams. Nested classification model was used to estimate to genetic correlation. Result of the research showed that the estimated value of genetic correlation from sire, dam, and sire-dam components were 0,32 ± 0,31; 0,52 ± 0,54, and 0,36 ± 0,52, respectively. It could be summarized that genetic correlation between birth and weaning weight of the sheep had a moderate positive. Birth weight characteristic could be used for criteria selection with non-direct selectionmethod for weaning weight.